Judy Moody Around the World in 8 1/2 Days [anglicky] / Book 7. - McDonald, Megan 1959- (Walker Books Ltd, 2019)
The new girl at school is so similar to Judy they are practically clones! Amy Namey is a member of the "way-cool" My-Name-Is-A-Poem Club, and what's more, she sounds just like Judy and likes the same things as her, too. Judy is meant to be doing an Around-the-World class project on Italy with her best-ever friends Rocky and Frank Pearl. But with so much time spent thinking about Amy, Judy's old friends start to feel left out...